Sex-specific interneuron vulnerability after traumatic brain injury correlates with neurotrophic signaling and chloride homeostasis, independent of behavioral and network outcomes - Consumi, Amandine; Marcourt, Cécile; Tnaimou, Tayam; Laurin, Jérôme; Schäfer, Michael K. E.; Pellegrino, Christophe; Rivera, Claudio (Frontiers in Cellular Neuroscience, 2025)
Traumatic brain injury (TBI) leads to persistent cognitive and emotional impairments, and growing evidence suggests that sex influences vulnerability through differences in neurotrophic signaling and chloride homeostasis. To investigate these mechanisms, we induced moderate TBI in male and female mice using the controlled cortical impact model and assessed outcomes 30 days post-injury. Behavioral performance was evaluated with the open field, elevated plus maze, and Barnes maze, while hippocampal oscillations, interneuron survival, protein expression (KCC2, NKCC1, p75NTR, BDNF), and transcriptomic profiles were analyzed. Locomotor activity was unaffected by TBI. Both sexes showed reduced latency to anxiogenic zones, but only females spent more time in the open arms, suggesting disinhibition. In the Barnes maze, both sexes exhibited spatial memory deficits: females showed early impairments with recovery, while males displayed persistent deficits. Electrophysiological recordings revealed increased theta and alpha power in both sexes, with greater variability in females. PV+ interneurons were selectively reduced in female hippocampi, accompanied by p75NTR upregulation, whereas males exhibited decreased BDNF. Transcriptomic analysis identified female-specific enrichment of calcium signaling, inflammation, and neurogenesis pathways, and NKCC1 upregulation occurred only in females. These findings reveal sex-specific interneuron vulnerability and molecular alterations after TBI, independent of overt behavioral and network outcomes, suggesting distinct mechanistic pathways that converge on similar functional phenotypes and underscoring the importance of sex-informed therapeutic strategies.